Roles of Host Nonhematopoietic Cells in Autoimmunity and Donor Cell Engraftment in Graft-versus-host Disease - Kim, Ju-Yang; Park, So-Hye; Kim, Hyun-A; Jung, Dae-Hee; Kim, Hyun-Ju; Choi, Hye-Jeong; Cho, Hong-Rae; Kwon, Byung-Suk (Immune network, 2010)
Graft-versus-host disease (GVHD) is initiated when alloreactive donor T cells are primed by host APCs to undergo clonal expansion and maturation. Since there is a controversy regarding the role of nonhematopoietic cells in GVHD, we wanted to investigate the influence of MHC disparity on nonhematopoietic cells on the pathogenesis of GVHD in the MHC-haplomismatched C57BL/6 (H-2(b)) or DBA/2 (H-2(d))-->unirradiated (C57BL/6xDBA/2) F(1)(BDF(1); H-2(b/d)) murine model of acute GVHD (aGVHD) or chronic GVHD (cGVHD). We generated (BDF(1)-->C57BL/6), (BDF(1)-->DBA/2), and (BDF(1)-->BDF(1)) chimeras and examined GVHD-related parameters and donor cell engraftment in those chimeras. Using this experimental system, we found that 1) severe aGVHD across MHC Ag barrier depends on the expression of nonhematopoietically rather than hematopoietically derived alloAgs for maximal GVHD manifestations; 2) host APCs were sufficient to break B cell tolerance to self molecules in cGVHD, whereas host APCs were insufficient to induce autoimmunity in aGVHD; 3) donor cell engraftment was greatly enhanced in the host with MHC-matched nonhematopoietic cells. Taken together, our results provide an insight into how MHC disparity on GVHD target organs contribute to the pathogenesis of GVHD.